Fikih Legal Opinion (Reinterpretasi Hukum Gadai dalam Perspektif Hukum Perdata dan Hukum Islam) - Miftahul Ulum (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2019)
Pawn is the right to a movable item that is attached to a person for assistance in the form of giving debt to another person. Submission of the movable goods by the person who owes the party giving the debt, is given as collateral. If in the future the debtor is defaulted, does not repay the debt when it is due, the collateral can be auctioned. Pawnshops based on the Civil Code Article 1150 are pocketing official permission to manage, assist, and develop all forms of financial activities by giving injections of funds to people in the form of financing. Auth (main tasks and functions) of pawning is protecting, fostering, and providing protection in the form of loan funds with the intent and purpose so that people are not caught up in various offers and financial assistance by non-formal financial institutions that relatively utilize the community, "strangling" with interest very high. Based on the analysis of the author's research, there are many non-formal financial institutions that provide loans with very high interest rates, this pattern of loans weighs heavily on society. This action is contrary to the law which aims to prosper society. The legal basis for shari'ah mortgage is to refer to the values ​​or norms contained in the DSN-MUI fatwa No. 25 / DSN-MUI / III / 2002 dated June 26, 2002 which confirms that it is permissible to borrow money by pawning goods as collateral for debt. However, at the perfective level of institutional governance, it is based on Government Regulation No. 10 of 1990 which was ratified on April 10, 1990.